Exploring self-concept, wellbeing and distress in therapeutic songwriting participants following acquired brain injury: A case series analysis. Issue 2 (7th February 2020) - Roddy, Chantal; Rickard, Nikki; Tamplin, Jeanette; Lee, Young-Eun C; Baker, Felicity Anne
ABSTRACT: Acquired brain injury (ABI) presents a significant threat to sense of self and necessitates a complex process of psychosocial adjustment. Self-concept changes remain understudied in the early stages of inpatient rehabilitation. The aim of the current study was to examine changes in self-concept, distress, wellbeing and functional skills for five inpatients undertaking a music therapy intervention within a subacute rehabilitation centre in Victoria, Australia. Participants completed a six-week, 12-session therapeutic songwriting programme to produce past-, current- and future-self-focused songs. A range of self-concept, subjective wellbeing and distress measures were completed pre-, mid- and post-intervention. A descriptive case series approach was applied to determine trends in pre-post scores for five individual cases. Participants showing the greatest gains across self-concept and subjective wellbeing indices also showed the greatest functional gains on the Functional Independence Measure (FIM) from admission to discharge. The current study highlights the importance of examining early changes in self-concept, wellbeing and distress in subacute rehabilitation, and suggests that individualised songwriting programmes warrant further research attention in neurological populations.